Cultural Tourism in the Belief about “Naga” of Thai Tourists in the Northeast (Udon Thani Province, Nongkhai Province, Bueng Kan Province, and Nakhon Phanom Province) Thailand - Sritalalai, Attapong (Dusit Thani College Journal, 2020)
This study has the following aims: 1) to study the behavior of domestic tourists visiting tourist attractions connected to a belief in Nagas in Northeast Thailand (Udon Thani, Nongkhai, Bueng Kan, and Nakhon Phanom provinces); and 2) to study the relationships between personal factors and tourists behaviors at tourist attractions connected to a belief in Nagas in Northeast Thailand (Udon Thani, Nongkhai, Bueng Kan, and Nakhon-Phanom provinces). This research was quantitative, involving the collection of data through questionnaires with 400 participants, and then analysis with descriptive statistics such as frequency, percentage, and Chi-Square test with a significance of 0.05. With regard to tourist behaviors, the study found that most tourists travel in order to relax and to gain knowledge and experiences from travelling. The tourist sites related to a belief in Nagas that have become the most popular for tourists are Kamchanod Forest in Udon Thani Province, and the festival of Naga fireballs (Bueng Fai Phaya Naga) on the 15th day of the 11th waxing moon, in Nong Khai province. The most common mode of travel is travel with family and friends. The decision to travel was usually the desire to travel to an area has to relationship to a belief in Naga. The most common size of groups of tourists travelling together is more than 5 people, followed by 2-3 people. Tourists most commonly spend between 5001 and 10,000 baht on trips to sites connected to a belief in Naga. The results of the Chi-Square test indicate that gender is has to relationship the length of the trip, and age is has to relationship the purpose of travel, the frequency of travel, the length of the trip, the number of people travelling together, and expenditure on travel. Marital status is has to relationship to the purpose of travel, the mode of travel, the frequency of travel, the length of the trip, the number of people travelling together and the expenditure on travel. Level of education is has to relationship to the reason for travel, the mode of travel, the frequency of travel, the length of travel, the number of people who travel together, and the expenditure on travel. Career is has to relationship to the sites that tourists visit, the length of trip, the number of people travelling together, and expenditure on travel. Average salary per month is has to relationship to the sites that tourists visit, the mode of travel, the frequency of travel, and the number of people who travel together, with a significance of 0.05